UJI PEMELIHARAAN IKAN PELANGI IRIAN (Melanotaenia boesemani) DI DALAM SISTEM RESIRKULASI [Study of Raibow Fish Culture (Melanotaenia boesemani) in Recirculation System] - Lukman Lukman (Jurnal Iktiologi Indonesia, 2005)
Irian rainbow fish (Melnnotnenia boesemani) is Papua ornamental fish. The culture problem of the fish has been low growth and survival rate, so that needed improvement to their culture method. Recirculation system can be an alternative model for the culture. The aim of research is to recognize growth characteristic of rainbow fish which be cultured on raceway model recirculation system. Oval shape pond used (300 x 120 cm²) by four partitioned, with water height 23.5 cm. Water flow moved by aerator and gravel was used for filter. The fish was stocked about 950 fishes, with length and weight average was 15.6 and 0.18 gram, respectively. Tubificidae was used for feed, in enough quantity. Research duration was two months, except fish observation until three months as support data. Sample of fish (5% of population) was measured their length-weight, and growth parameters was analyzed. Several water quality parameters measured, namely temperature, pH, dissolved oxygen, nitrite and ammonia content, and Chemical Oxygen Demand. Water quality condition on suitable during observation. Survival rate of fish reached 79%, growth rate was low (a =0.70% ), and indicated decrease of length growth on third month. Feed efficiency (e) was very low (4.15%) with food conversion ratio 13.4. Length-weight relationship indicated high linier relation (R>0.86) except on beginning observation (R = 0.55). Fish length groups indicated wider distribution parallel to increase of age.